Single Blind Randomized Controlled Trial of Modified Constraint-Induced Movement Therapy in Infants With the Sequelas of Unilateral Brachial Plexus Injury - Cui, Zhenzhen; Liu, Le; Chen, Xi; Zeng, Haiyan; Zheng, Shizhu; Wu, De (Frontiers in Human Neuroscience, 2022)
Objective: To explore the effect of modified constraint-induced movement therapy (mCIMT) on upper limbs residual dysfunction for infancy with the sequelas of unilateral brachial plexus injury (uBPI). Methods: Single blind randomised controlled trial of mCIMT versus standard care. An enrolling 31 infants with a uBPI exhibiting residual dysfunction of the affected upper limb for over 6 months was conducted. And functional outcomes pertaining to the affected upper limb were assessed via AMS, GRES, RHS, and MSS at 0, 3, and 6 months after treatment. Results: No differences were found in baseline (acquisition phase) AMS, MSS, GRES, or RHS between the control and mCIMT groups (F(1,14)=0.062,P=0.086; F(1,14)=0.483,P=0.499; F(1,14)=0.272,P=0.610; Z=-0.336, P=7.373). At the 3- and 6-month follow-up time points, AMS, MSS and GRES scores were significantly improved over baseline in both groups (mCIMT: F(2,30)=183.750, 128.614, 110.085, P<0.05; Control: F(2,28)=204.007, 75.246, 51.070, P<0.05). No significant differences were found between two treatment groups at the 3-month follow-up time point (F(1,14)=0.565,P=0.465; F(1,14)=0.228,P=0.641; F(1,14)=0.713,P=0.413; Z=-0.666, P=0.505). However, at the 6-month follow-up time point, AMS and MSS scores were significantly improved in the mCIMT group relative to the control group (F(1,14)=8.077,P=0.013; F(1,14)=18.692,P=0.001). Conclusions: mCIMT may benefit the rehabilitation of residual upper limb dysfunction associated with a uBPI in infants.